Intermodality and the changing role of Nodes in transport networks - Roberto Roson; Stefano Soriani (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper analyses some of the economic issues involved in the diffusion of modern intermodal technologies and the impact of intermodality on the functions performed by nodes in transportation networks. Two simple economic models are presented: the first considers why an intermodal transport service may be chosen instead of traditional single modal services, while the second addresses the link between standardisation and warehousing. The last section focuses, in a less abstract and more detailed way, on the maritime transport sector. The aim is to find evidence for the effects highlighted by the models.
Keywords: L9; R4; 330; Intermodality; maritime transport; transport networks; Kombinierter Verkehr; Theorie